Shear Behavior of Fibrous High Strength Concrete Deep Beams Under Uniformly Distributed Loading - Hanna, Thamer H. (Sulaimani Journal for Pure and Applied Sciences, 2007)
This paper investigates the effect of the steel fiber and type of web reinforcement of high strength concrete on cracking behavior and deformation characteristics of deep beams under uniformly distributed load. The complete load-deflection response and the modes of failure were investigated experimentally. Eighteen beams of (600*300*100 mm) and nine cubes of (150*150*150 mm) in dimension were tested and compared with the same three series of different types of web reinforcement which contain different contents of fiber as additive, Results indicate that mid-span deflection decreases with increasing fiber content, while shear capacity increases, also test results indicate that type of web reinforcement produces no effect on formation of vertical cracks.
Keywords: Deep beam High strength concrete Steel fiber Shear capacity